2019
DOI: 10.1002/ldr.3481
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of long‐term ditch‐buried straw return on soil bacterial community in a rice–wheat rotation system

Abstract: Ditch‐buried straw return (DB‐SR) is a novel soil tillage and fertility building practice that is effective in regulating soil carbon and nitrogen dynamics and hydrothermal processes in rice–wheat rotation systems. However, the effects of DB‐SR on soil bacterial community are still largely unclear. We deciphered soil bacterial community with high‐throughput sequencing under various returning approaches, burial depths, and straw amounts after 6.5 years of DB‐SR application. Our results showed that DB‐SR structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 68 publications
6
9
0
Order By: Relevance
“…Fungi are the dominant fauna degrading crop straw. Returning straw to the field can increase the diversity and the activity of soil fungi, especially the ratio of fungi to bacteria (Yang et al, 2020b). In this study, the presence of straw significantly increased the Sobs and Shannon indices, indicating that straw return increased the diversity of soil fungi.…”
Section: Diversitysupporting
confidence: 48%
“…Fungi are the dominant fauna degrading crop straw. Returning straw to the field can increase the diversity and the activity of soil fungi, especially the ratio of fungi to bacteria (Yang et al, 2020b). In this study, the presence of straw significantly increased the Sobs and Shannon indices, indicating that straw return increased the diversity of soil fungi.…”
Section: Diversitysupporting
confidence: 48%
“…It is interesting to highlight that soil parameters such as TOC and some nutrients like TN, Mg and B were associated with changes in soil bacterial community, although this association was not observed in the fungal community. Similar results were observed by Yang et al [60] and Zhang et al [61] who found a link between the bacterial community and soil chemical properties. Organic carbon is considered necessary to alter microbial community regardless other factors [62] and is well known that compost enhance carbon and nitrogen in soils for microbial communities [63].…”
Section: Discussionsupporting
confidence: 90%
“…Gemmatimonadetes are considered as oligotrophic organisms (Pascault et al, 2013). Negative relationships were observed between Gemmatimonadetes and SOC (Yang et al, 2020). In addition, Gemmatimonadetes act as a generalist and can adapt to the various edaphic environments, such as low soil moisture, anoxic conditions and a wide range of nutrient concentrations (DeBruyn et al, 2011).…”
Section: Fungi Diversity and Bacterial Phyla Are The Major Drivers Of Soil Multifunctionalitymentioning
confidence: 99%